2017
DOI: 10.1101/lm.044289.116
|View full text |Cite
|
Sign up to set email alerts
|

Novelty and fear conditioning induced gene expression in high and low states of anxiety

Abstract: Emotional states influence how stimuli are interpreted. High anxiety states in humans lead to more negative, threatening interpretations of novel information, typically accompanied by activation of the amygdala. We developed a handling protocol that induces long-lasting high and low anxiety-like states in rats to explore the role of state anxiety on brain activation during exposure to a novel environment and fear conditioning. In situ hybridization of the inducible transcription factor found increased gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 126 publications
(171 reference statements)
1
4
0
Order By: Relevance
“…This expression is likely not required for the acquisition or consolidation of the context representation, as intra-amygdala NMDAR antagonism or anisomycin administration during context preexposure has no effect on the CPFE (Huff & Rudy, 2004; Matus-Amat et al, 2007). Our findings are consistent with prior work demonstrating that novelty (e.g., during novel context exposure or handling) drives gene expression in the lateral nucleus of the amygdala (Alberini, 2009; Asok et al, 2013; Donley & Rosen, 2017; Rosen et al, 1998). Following training with or without a post-shock freezing test, BLA c-Fos , Arc , Egr-1 , and Npas4 expression was significantly elevated in the Pre and Alt-Pre groups above HC baseline.…”
Section: Discussionsupporting
confidence: 92%
“…This expression is likely not required for the acquisition or consolidation of the context representation, as intra-amygdala NMDAR antagonism or anisomycin administration during context preexposure has no effect on the CPFE (Huff & Rudy, 2004; Matus-Amat et al, 2007). Our findings are consistent with prior work demonstrating that novelty (e.g., during novel context exposure or handling) drives gene expression in the lateral nucleus of the amygdala (Alberini, 2009; Asok et al, 2013; Donley & Rosen, 2017; Rosen et al, 1998). Following training with or without a post-shock freezing test, BLA c-Fos , Arc , Egr-1 , and Npas4 expression was significantly elevated in the Pre and Alt-Pre groups above HC baseline.…”
Section: Discussionsupporting
confidence: 92%
“…CA extracts and their active compounds have known anxiolytic effects [ 14 , 15 , 16 ]. Reducing anxiety during the CFR test should either reduce fear acquisition [ 17 , 18 ] or have no effect [ 19 ]. However, in this study we observed an increase in fear response with all treatments in male 5XFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have blurred the classic distinction between the innate and adaptive immune systems as well (110,111). This idea notwithstanding, more complex forms of learning, such as classical or operant conditioning, may utilize circuits that are parallel to those that mediate innate forms of the modified behavior, as shown in the case of conditioned vs. unconditioned fear (112)(113)(114). In this context, it is worth noting that mice can learn an instrumental, operant response using successful aggressive encounters as a reinforcer (115), and that performance of this instrumental task is facilitated by optogenetic activation of VMHvl neurons (116).…”
Section: Discussionmentioning
confidence: 99%